PERSPEKFTIF HINDU MENGENAI SIFAT DAN KEMAHAKUASAAN TUHAN - Ni Putu Dian Utami Dewi; Kadek Ari Cahyadi; Luh Juni Lestari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Hinduism is familiar with the concepts of Monotheism, Pnatheism and Politheism, understanding that God is only one truth, not the second. but the name of God or God is a manifestation of the form of God in the form of saguna brahman or the energy of God which is permeated immanently in the human spiritual soul. this saguna concept is a form of personifying God that is useless (God who is formless, undefiled, has no beginning and no end, is not bound by time and change, God is everywhere - everywhere. God animates all forms in the universe. Hindu people make forms of worship on the grounds of God's personified form which is realized to make it easier to connect devotional services to God. in Bgavad Gita 14. 3 explained All material, called Brahman, is the source of birth, and I say that Brahman contains, which enables the birth of all living things, O son of Bharata. Clearly illustrated in the sloka everything that exists, created, the living and the dead is at the will of God Almighty.